2013
DOI: 10.3892/mmr.2013.1531
|View full text |Cite
|
Sign up to set email alerts
|

Swimming exercise alleviates the symptoms of attention-deficit hyperactivity disorder in spontaneous hypertensive rats

Abstract: Attention-deficit hyperactivity disorder (ADHD) is a neurobehavioral disorder characterized by inattention, hyperactivity and impulsivity. In the present study, we investigated the effects of swimming exercise on the symptoms of ADHD in correlation with the expression levels of dopamine and the dopamine D2 receptor. Adult male spontaneous hypertensive rats (SHRs) were used as animal models of ADHD and Wistar-Kyoto rats were used as controls. The activity, impulsivity and levels of non-aggressive and aggressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 45 publications
1
34
0
1
Order By: Relevance
“…32,33 In an animal study, Ko et al reported that swimming exercise improves ADHD symptoms by upregulating dopamine expression and downregulating dopamine D2 receptor expression. 34 Tantillo et al suggested that physical exercise acts as a dopaminergic adjuvant in the treatment of behavioral disturbances in patients with ADHD. 35 In this context, Kang et al demonstrated a positive correlation between physical exercise and improved attention and cognitive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 In an animal study, Ko et al reported that swimming exercise improves ADHD symptoms by upregulating dopamine expression and downregulating dopamine D2 receptor expression. 34 Tantillo et al suggested that physical exercise acts as a dopaminergic adjuvant in the treatment of behavioral disturbances in patients with ADHD. 35 In this context, Kang et al demonstrated a positive correlation between physical exercise and improved attention and cognitive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…As the method described previously [ 20 , 23 ], we performed immunohistochemistry to detect the expression of 5-HT, TPH, and TH. The tissue sections were treated with mouse anti-TH, mouse anti-TPH, and rabbit anti-5-HT antibody (1:1,000; Santa Cruz Biotechnology, Santa Cruz, CA, USA) during overnight.…”
Section: Methodsmentioning
confidence: 99%
“…As the method described previously [ 20 , 23 ], Western blotting was conducted to evaluated D1 dopamine receptor expression in the PFC, striatum, and SN. After dissecting PFC, striatum, and SN, these tissues were collected.…”
Section: Methodsmentioning
confidence: 99%
“…Sport soll ebenfalls einen positiven Einfluss auf die ADHS-Symptomatik haben. Im Tiermodell mit hyperaktiven Ratten führte körperliche Aktivität zu einer verminderten Hyperaktivität, Impulsivität und einer geringeren Aggressivität der Tiere (38). Bei einer Untersuchung von Erwachsenen mit ADHS konnte außerdem gezeigt werden, dass Sport zu einem Rückgang von Impulsivität, intrusiven Gedanken sowie Sorgen führt (39).…”
Section: Weitere Behandlungsmöglichkeitenunclassified